Research on the Construction and Prediction of China's National Fitness Development Index System Under Social Reform - Liu, Zheng; Zhang, Shijia; Li, Lingling; Hu, Bin; Liu, Ran; Zhao, Zhao; Zhao, Yuanjun (Frontiers in Public Health, 2022)
Background: National fitness is a development plan formulated by China to promote people's participation in leisure and fitness, enhance people's physique and realize the general goal of strengthening sports. Methods: Based on combing the development process of national fitness in New China, using the improved "balanced scorecard" method, this paper constructs an evaluation index system of national fitness development index. Results: The national fitness development Index was established, including 4 first-level indicators, 14 second-level indicators and 49 third-level indicators. It can calculate the national fitness development index with a total score of 100 points. Conclusion: In order to verify the feasibility of the evaluation system, the goal current situation evaluation method is used to calculate the national fitness development index during the 14th Five Year Plan period based on the development of national fitness during the 13th Five Year Plan period, to provide evaluation tools and theoretical reference for the development of national fitness in China.